Impact of Gut Recolonization on Liver Regeneration: Hepatic Matrisome Gene Expression after Partial Hepatectomy in Mice - Abdul Rahman Amin; Raman Nur Fatin Aqilah; Beth L. Mallard; Fergus Shanahan; Antony M. Wheatley; Mohd Hairulhisyam Ngatiman; Nur Fariha Mohd Manzor; Marlini Muhamad (MDPI, 2024)
Indexed by WOS/Scopus